Modos I y II de producción de conocimiento como ideologías problemas y perspectivas - Paz Samudio, Alfonso (Universidad Santiago de Cali, 2017)
This work seeks to reinterpret the modes I and II of the knowledge produc-tion (Gibbons et al., 1994) as ideologies, the first with origins in the academic world and the second coming of the business world. A version of the philo-sophy and history of science of the modernity and its inevitable exhaustion and crisis, inspired by Castoriadis, Arendt and Boaventura De Sousa Santos is based. Alternatively an ideology of the production, distribution, appropria-tion and assessment of the knowledge and the knowledge that is based on the world of the life of Husserl, and the human condition and the spirit of Arendt arises to contribute to strengthen the project of individual and social autonomy in higher education. Finally, the conclusions and recommendations seeks to achieve the fulfilment of the objectives initially proposed.